PENGARUH KESADARAN MEREK DAN PERSEPSI KUALITAS TERHADAP CITRA MEREK SERTA DAMPAKNYA TERHADAP MINAT BELI (Studi Pada Konsumen Produk Sepatu Bata - Kevin Evan Adriano; Cahyaningratri Cahyaningratri (Diponegoro Journal of Management, 2022)
The problem in this research is that there is a drastic decrease in sales of Bata Shoes from 2015 to 2020, which indicates the possibility of a decrease in purchase intention from shoe consumers for Bata Shoes products in Indonesia. This problem is also relevant to the Bata brand being ranked 1 in the Top Brand Index and being the market leader in the last 5 years, but always experiencing a decrease in the percentage of the Top Brand Index. In 2017, Bata Shoes was ranked first with a Top Brand Index percentage of 19.3%. In the following years, the percentage of the Top Brand Index of Bata shoes continued to decline to 12.5% in 2020. Based on gap research, it was also found that there was an alleged influence of brand awareness and perceived quality on brand image and brand image on consumer purchase intention in Bata Shoes. This study aims to analyze the effect of brand awareness and perceived quality on brand image and purchase intention, also brand image on consumer purchase intention in Bata Shoes. The population used in this study were shoe consumers in Indonesia. The sampling technique used is purposive sampling. The samples taken were 246 research respondents. The data collection method in this study used a questionnaire. The data analysis method uses structural equation modeling. The results of this study are brand awareness and perceived quality have a positive effect on brand image and brand image has a positive effect on consumer purchase intention in Bata Shoes. In addition, brand awareness has a positive and significant effect on consumer purchasing interest while quality perception does not have a significant effect on consumer purchase intention.